If it's not what You are looking for type in the equation solver your own equation and let us solve it.
10x+17=6x+69
We move all terms to the left:
10x+17-(6x+69)=0
We get rid of parentheses
10x-6x-69+17=0
We add all the numbers together, and all the variables
4x-52=0
We move all terms containing x to the left, all other terms to the right
4x=52
x=52/4
x=13
| (x-1/2)^2-9=0 | | (x-19)^2=0 | | (x-1/2)^2=9 | | x+(-30)=60 | | 6x-11=42 | | 1,2(2x-2,3)+1,5(x-0,8)+1,6=3,5(3x-5,2) | | 10+2a=18 | | 7x=9x-30 | | -12r+4=190 | | x^2+83=0 | | 6x2-7x+8=0 | | 7=x=11 | | 3(3x^2)=42 | | 7+3x=2x÷13 | | 22-2x-8=7+3x | | 8(7x+2,2)-5(12x-1,8)-21=12(2x+0,2)-36 | | 5x+7=x-25 | | 3x-3x=48 | | X+2=2x+14 | | 6/35=x | | 12/x=70 | | 17x19=323 | | 13x-25=3x-4 | | 14=6n+-2n | | -4x+3=-7x-1 | | 2x+1=13x-8=0 | | 3n−7=26 | | 2x+113x-8=0 | | 2/x=1,75 | | x=10.5+0.5x | | x=10.5+05x | | u+5=27/3 |